HUBUNGAN KELINCAHAN DAN KECEPATAN LARI DENGAN KETERAMPILAN MENDRIBLING DALAM PERMAINAN SEPAK BOLA PADA SISWA PUTRA KELAS VIII MTS AL MUTTAQIN KOTA PEKANBARU - Haryanto, Tri; ', Saripin; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this research is the relationship of agility and speed to run with dribbling skills. This research is correlational research with the entire population of eighth grade boys MTS AL Muttaqin totaling 48 people. The sampling technique in this study is the total sampling. This study aims to determine the relationship between agility with the ball skills mendribling eighth grade students MTS Al Muttaqin, to determine the relationship between running speed with the ball skills mendribling eighth grade students MTS Al Muttaqin, to determine the relationship between agility and speed to run with the ball skills mendribling the eighth grade students of MTS Al Muttaqin. From the results obtained have a relationship with a running speed dribbling skills in the game of football student MTS Al Muttaqin with a correlation value of 0.54. From the results obtained agility have a relationship with the students' ability dribling MTS Al Muttaqin with a correlation value of 0.58. There is a relationship between the jointly run the agility and speed dribbling skills in the game of football student MTS Al Muttaqin with a correlation value of 0.68.Key word: Agility, Sport Run, Dribbling